Raising TOEFL Awareness: An Introduction to Its Importance and Benefits for Senior High School Students at SMA Swasta Teladan Pematangsiantar - Napitu, Nauli Hosianna; Sinaga, Monika; Sihotang, Elina; Sebayang, Santa Nananda; Herman, Herman (Universitas Ibn Khaldun, 2025)
TOEFL introduction and awareness activity aimed to deepen students' understanding at SMA Swasta Teladan Pematangsiantar about the importance of English proficiency globally, especially through the Test of English as a Foreign Language (TOEFL). The activity addressed the low awareness among high school students regarding TOEFL certification as an academic and professional requirement both nationally and internationally. The method used a descriptive qualitative approach with interactive presentations, Q&A sessions, and a brief TOEFL simulation. Data was collected through direct observation of student engagement and feedback during discussions. Presentation media and simplified TOEFL practice questions were the primary instruments. Results showed high enthusiasm among students, many of whom had just realized TOEFL's significance for higher education and career prospects. Some students expressed interest in learning more about TOEFL sections such as Listening, Structure and Written Expression, and Reading Comprehension. The activity also proved that interactive methods effectively captured students’ attention and increased their linguistic awareness. In conclusion, the TOEFL socialization successfully provided essential insight into TOEFL benefits and motivated students to prepare early for future academic and professional challenges. It is recommended that such activities continue regularly with expanded content, personalized mentoring, and more intensive test preparation support to help students meet global standards in English proficiency.